Establishment and Practice of Rehabilitation Therapy Professional Graduation Examination Norms - Qiang TANG; Yan WANG; Luwen ZHU; Lei WANG; Bin ZHAO; Huijie CHEN (康复学报)
Based on the objective structured clinical examination (OSCE) method and physician qualification tests models, Heilongjiang University of Traditional Chinese Medicine proposed a “five-step” integrated assessment model as rehabilitation therapy professional graduation examination method. According to the weakness of talents cultivation as well as advantages and disadvantages of the assessment model found in application process, reasonable rehabilitation therapy graduation examination norms were estabilished to cultivate the students' ability of theory combined with practice, and analyzing and solving problems, improve comprehensive qualities of students and cultivation quality of rehabilitation talents, provide information for rehabilitation professional teaching reform, and promote the development of rehabilitation education.